Tramadol - Upadhyay, DK; Palaian, S; Kishore, PV; Paudel, R; Prabhu, M; Shankar, PR; Mishra, P (Journal of Institute of Medicine Nepal, 2007)
Background: Tramadol is a centrally acting synthetic opioid analgesic used orally and parenterally in pain management. The United States Food and Drug Administration (US FDA) has approved Tramadol for the management of moderate to severe pain. Tramadol has minimal sedation and respiratory depression and has less gastrointestinal effect. It produces nausea, vomiting, dizziness, headache, somnolence, vertigo, seizures, etc. Concomitant use of Tramadol with CNS depressants should be avoided because Tramadol may potentiate the respiratory and CNS depressant effects of these drugs. There is an increase risk of convulsions in patient with epilepsy or history of seizures. It is contraindicated in patient receiving warfarin because it prolongs international normalized ration (INR) and prothrombin time and extensive ecchymoses. The concomitant use of Tramadol and serotonergic agents (e.g. Mirtazipine, Selegiline, Venlafaxine etc) is contraindicated because of the risk of serotonin syndrome. It has also got significant drug abuse potential. In Nepal, Tramadol is available as 50 mg capsule and 100 mg controlled release tab. It is also available as 50 mg and 100 mg injection. The safety profile, contraindications, drug interactions and the economic parameters should be considered before prescribing Tramadol. Keywords: Contraindications, Indications, Painmanagement, Tramadol The full text of this paper is available at Journal of Institute of Medicine website